NIGERIAN POLITICAL RHETORIC ON APC’S 2023 MUSLIM-MUSLIM CANDIDACY: A COMPARATIVE ANALYSIS OF DOGARA’S AND SHETTIMA’S DISCOURSE - IDRIS, Adamu; BABURA, Adamu Isah (EBSU Journal of Social Sciences and Humanities, 2024)
Language is considered a vital weapon in the armory of political orators, who often deploy different rhetorical tactics aimed at swaying audience and winning them over to preferred positions. This thus, remains a major focus of attention among discourse analysts. The Muslim-Muslim presidential candidacy in Nigeria during the 2023 general elections formed a political incident that attracted heated rhetoric, especially between the Muslims and Christians in the North. In relation to this, this study bridged some gaps in research to explore how the vice-presidential candidate, Kashim Shettima and Yakubu Dogara, the northern Christian advocate, deployed rhetorical tactics in attempts to influence Nigerians. Therefore, this study drew on Critical Discourse Analysis through Van Leeuwen’slegititmation and deligitimation theory to analyze Shettima’s and Dogara’s speeches on Muslim-Muslim ticket. Results discovered that while Shettima employed variety of rhetorical tactics to rationalise the Muslim-Muslim candidacy and encourage Nigerians to support it, Dogara deployed numerous tactics to delegitimise it and urged Christians to work against its success in the Nigeria’s 2023 general elections.